Histological Changes in The Liverof Mice Treated with Cadmium - Albir, Ahmed (Iraqi Journal of Science, 2023)
The present study was conducted using 15 adult male Swiss albino mice (weighing 35-45g). They were equally divided into three experimental groups. The first group was only given water as control during experimentation period (28days). Both of the second and third groups of mice were daily given a subcutaneous injection of cadmium as cadmium chloride (CdCl2) at a dose of 2mg and 4 mg Cd/Kg body weight respectively. The examination of the histological sections of the second experimental group of mice showed abundant histological changes in the hepatocytes such as increased size, presence of spaces and dense appearance of the cytoplasm, whereas these changes were more abundant in the hepatocytes of the third experimental group of mice in comparison with the second experimental group such as increased size and tubular- shaped hepatocytes, presence of spaces and dense appearance of the cytoplasm.